ANALYSIS OF ENGLISH LEARNING DIFFICULTIES OF STUDENTS AT MTS PONDOK PESANTREN DDI PATOBONG - Muh Afiz; Syaiful Syaiful (STKIP Darud Da'wah Wal Irsyad Pinrang, 2026)
Learning difficulties have significant impacts on students’ English learning capabilities. This study investigated students’ difficulties in learning English and the factors contributing to these difficulties at MTs Pondok Pesantren DDI Patobong. The methodology used in this research was qualitative descriptive design. The participants consisted of one English teacher and five students from class VIII.A. Data were collected through interviews and analysed using data reduction, data display and conclusion drawing techniques. The findings showed that the students experienced difficulties in three main aspects. First, in the cognitive aspect, students had limited vocabulary, which hindered their understanding of English words and meanings. Second, in affective aspect, students experienced difficulties to finish task independently. Third, in the psychomotor aspect, students lacked self-confidence in speaking English and explaining the materials in English. The study further found that students’ learning difficulties were influenced by internal factors, especially low intrinsic motivation, and external factors related to school environment. However, English learning activities conducted in the school environment also contributed positively to students’ improvement in learning English.